2017
DOI: 10.1002/brb3.828
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal western‐type diet and associated gestational weight gain alter postpartum maternal mood

Abstract: IntroductionThe role of perinatal diet in postpartum maternal mood disorders, including depression and anxiety, remains unclear. We investigated whether perinatal consumption of a Western‐type diet (high in fat and branched‐chain amino acids [BCAA]) and associated gestational weight gain (GWG) cause serotonin dysregulation in the central nervous system (CNS), resulting in postpartum depression and anxiety (PPD/A).MethodsMouse dams were fed one of four diets (high‐fat/high BCAA, low‐fat/high BCAA, high‐fat, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 93 publications
(112 reference statements)
1
18
0
1
Order By: Relevance
“…Decreased striatal DA has also been observed in BALB/c mice, "poor mothers" that develop depressive-like behavior following pregnancy and delivery (Avraham et al 2017). Other work using the gestational stress (Leuner et al 2016) and high-fat diet (Bolton et al 2017) models of PPD further point to altered DA signaling in the NAc and other VTA targets. DA dysfunction would also be predicted in endocrine models of PPD since sex steroid hormones and stress hormones modulate the reward system and influence reward behavior (Brummlete and Galea 2010; Montoya et al 2014;Macoveanu et al 2016), but this hasn't been examined.…”
Section: The Reward System In Ppd: Animal Modelsmentioning
confidence: 94%
See 1 more Smart Citation
“…Decreased striatal DA has also been observed in BALB/c mice, "poor mothers" that develop depressive-like behavior following pregnancy and delivery (Avraham et al 2017). Other work using the gestational stress (Leuner et al 2016) and high-fat diet (Bolton et al 2017) models of PPD further point to altered DA signaling in the NAc and other VTA targets. DA dysfunction would also be predicted in endocrine models of PPD since sex steroid hormones and stress hormones modulate the reward system and influence reward behavior (Brummlete and Galea 2010; Montoya et al 2014;Macoveanu et al 2016), but this hasn't been examined.…”
Section: The Reward System In Ppd: Animal Modelsmentioning
confidence: 94%
“…In another stress-based PPD model, exposure to early life stressful experience is utilized (Nephew et al 2017a). Recent attempts have also been made to develop models of maternal depression based on high-fat diet/obesity, another factor which increases risk for PPD (Perani et al 2015;Bolton et al 2017). Each of these models induces one or more critical aspects of postpartum depressive-like symptomology including behavioral despair, anhedonia, anxiety-like behavior, and/or impaired maternal care which like the human condition can negatively impact offspring neurodevelopment (Smith et al 2004;Champagne and Meaney 2006;Brummelte et al 2006;Babb et al 2014).…”
Section: Animal Models Of Ppdmentioning
confidence: 99%
“…The specific factors contributing to the greater risk of PAAD include the absence of the partner or family support, a previous history of mental disorder or domestic violence, alcohol abuse, occurrence of pregnancy complications, changes estradiol and progesterone, and high intake of processed foods with excess sugar and fat content [1, 68]. One recent investigation showed that the perinatal consumption of a Western-type diet induced postpartum mood disorders, as well as depression-like phenotype and anxiety-like behavior in mice [9].…”
Section: Introductionmentioning
confidence: 99%
“…Another study by Perani and colleagues showed that HFD prevented lactation-associated anxiolysis, with HFD-fed mouse dams showing an increase in the latency to enter the lit chamber of the light-dark box, and a decrease in the number of lit chamber entries [74]. Similarly, a study investigated the effects of various maternal diets in mice showed that intake of a diet high in fat and branched-chain amino acids reduced time spent in open arms on P8 [14]. In our studies, we failed to see robust effects of diet in the open field test.…”
Section: Effects Of Diet and Selective Breeding On Behavioral Profile Of Postpartum Damsmentioning
confidence: 97%